Impaired Cerebral Vasomotor Reactivity in Alzheimer’s Disease - Góngora Rivera, Juan Fernando; Cordero Pérez, Adolfo; González Aquines, Alejandro; Anaya Escamilla, Antonio; Villarreal Garza, Eduardo; Espinosa Ortega, Meztli; Salinas Carmona, Mario César; Ortiz Jiménez, Xóchitl A. (2018)
Background. Recent studies have shown that cerebral vascularity may be impaired in Alzheimer’s disease. Cerebral vasomotor reactivity could be an important biomarker for this pathology. Aims. The aim of this study was to investigate the alterations in cerebral vascular motorre activity in Alzheimer’s disease subject sand to associate the sechanges with the ir cognitivescores. Methods. We recruited subjects with a diagnosis of Alzheimer’s disease and healthy controls. Demographic, clinical, imaging, and cognitive test were obtained. Then all participants performed a cerebral vascular motorre activity test with 7% CO2 and cerebral blood flow velocities (CBFV) were recorded with transcranial doppler ultrasound before and after the test. Results. Wer ecruited 45 subjects, 26 (21 female) Alzheimer’s disease participants and 19 (15 female) healthy controls. There were no differences in baseline cerebral blood flow velocities between the groups. After the cerebral vasomotor reactivity test, absolute mean difference in mean CBFV (ΔCBFV-m)was 8.70±4.14 versus4.81±6.96 (p<0.01), respectively. Calculated percentage of change (%CVMR) was lower in the ADgroup7.45±18.25versus23.29±17.48, and there was a positive but weak correlation with mini-mental scores.